Pelatihan “Giving and Asking for Direction” untuk Mengenalkan Kearifan Budaya Lokal Melalui Film Pendek : Kegiatan ABDIMAS di SMA Fons Vitae 1 Jakarta - Putri Rindu Kinasih; Junita Junita (Lembaga Pengembangan Kinerja Dosen, 2026)
Currently, the skills needed to advance a tourist area are influenced by the availability of human resources who can speak English and understand local culture well. Unfortunately, improving English proficiency remains a challenge. Additionally, another issue appears as the Alpha generation is exposed to a great deal of English-language social media content; however, this does not appear to be directly correlated with an improvement in their English proficiency. It appears that the English Club instructors at SMA Fons Vitae 1 Jakarta were also aware of these two problems. Therefore, on September 11, 2025, an ABDIMAS activity entitled